USP26 regulates TGF-ß signaling by deubiquitinating and stabilizing SMAD7 - Kit Leng Lui, S.; Iyengar, P.; Jaynes, P.; Isa, Z.; Pang, B.; Tan, T.; Eichhorn, Pieter (Wiley-Blackwell Publishing Ltd., 2017)
© 2017 The Authors. Published under the terms of the CC BY 4.0 license The amplitude of transforming growth factor-ß (TGF-ß) signal is tightly regulated to ensure appropriate physiological responses. As part of negative feedback loop SMAD7, a direct transcriptional target of downstream TGF-ß signaling acts as a scaffold to recruit the E3 ligase SMURF2 to target the TGF-ß receptor complex for ubiquitin-mediated degradation. Here, we identify the deubiquitinating enzyme USP26 as a novel integral component of this negative feedback loop. We demonstrate that TGF-ß rapidly enhances the expression of USP26 and reinforces SMAD7 stability by limiting the ubiquitin-mediated turnover of SMAD7. Conversely, knockdown of USP26 rapidly degrades SMAD7 resulting in TGF-ß receptor stabilization and enhanced levels of p-SMAD2. Clinically, loss of USP26 correlates with high TGF-ß activity and confers poor prognosis in glioblastoma. Our data identify USP26 as a novel negative regulator of the TGF-ß pathway and suggest that loss of USP26 expression may be an important factor in glioblastoma pathogenesis.